Diagnostic And Treatment Protocol Adopted by Private Practitioners of Surat City for Drug Resistant Tuberculosis Patients - Patel, Prakash B; Rana, Jayesh J; Bansal, R K (National Journal of Community Medicine, 2015)
Introduction: This study explores the practices adopted by Private Practitioners for diagnosis and management of Drug Resistant Tu- berculosis patients in Surat city of Western India. Methodology: In this descriptive cross sectional study of Private Physicians of Surat city were selected randomly from IMA Surat member list. A pre-test questionnaire including Profile of the doc- tor, Profile of patients suspected for MDR TB, Diagnostic & Treat- ment practices and Follow up issues was used to collect data. Data Analysis was done using Epi-info software calculating descriptive statistics. Results: Most common investigative methods used by private phy- sicians to diagnose MDR TB were sputum microscopy, x-ray chest and sputum culture. Commonly used second line drugs for MDR TB patients were Fluoroquinolones, Aminoglycosides and Ethion- amide. Nearly three forth physicians preferred 4 or more drug combination for MDR TB treatment. Most of them preferred 2 or 3 second line drugs in their prescriptions. Common investigations preffered by them during follow up were Sputum AFB, Culture and Chest X-Ray. Conclusion: Compliance to recommended standards of MDR TB management was common among the private physicians but quite a few were unacceptable in context of WHO recommendations. There is need to streamline these protocols according to the general guideline for MDR TB management.